2004
DOI: 10.1088/0268-1242/19/5/008
|View full text |Cite
|
Sign up to set email alerts
|

Hall effect and band structure of p-CdSb in strong magnetic field

Abstract: The Hall effect in the anisotropic II-V group semiconductor p-CdSb is investigated at temperatures between T = 3.6 and 200 K and pulsed magnetic fields up to B = 25 T in unintentionally doped samples oriented along the crystallographic axes [100] and [010]. The Hall coefficient, R(B, T ), with B [001] exhibits in low fields a flat region followed by a descending interval when B is increased. This behaviour is attributed to the presence of two groups of holes with concentrations p 2 (T ) > p 1 (T ) and mobiliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…On the other hand, it has been shown that already in the pure as-grown ZnSnAs 2 film the observed dependences of µ(T) and p(T) satisfy reasonably those of the two-band conduction mechanism, taking into account the holes in the valence band and in the acceptor band [26]. It is worth mentioning the two-band conduction, observed in the II-V semiconductor CdSb [27] and in the III-V based In 1-x Mn x Sb [28], permitting a detailed quantitative explanation of the resistivity and the Hall effect data in strong magnetic fields. The situation with the transport data in the ZnSnAs 2 + MnAs samples at this point is even more complicated than in a pure ZnSnAs 2 compound, suggesting existence of an additional conduction channel or additional type of carriers, associated with MnAs inclusions and having concentrations and mobilities, which differ drastically from those in the pure ZnSnAs 2 compound.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 58%
“…On the other hand, it has been shown that already in the pure as-grown ZnSnAs 2 film the observed dependences of µ(T) and p(T) satisfy reasonably those of the two-band conduction mechanism, taking into account the holes in the valence band and in the acceptor band [26]. It is worth mentioning the two-band conduction, observed in the II-V semiconductor CdSb [27] and in the III-V based In 1-x Mn x Sb [28], permitting a detailed quantitative explanation of the resistivity and the Hall effect data in strong magnetic fields. The situation with the transport data in the ZnSnAs 2 + MnAs samples at this point is even more complicated than in a pure ZnSnAs 2 compound, suggesting existence of an additional conduction channel or additional type of carriers, associated with MnAs inclusions and having concentrations and mobilities, which differ drastically from those in the pure ZnSnAs 2 compound.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 58%
“…the behavior of ρ (T) at B = 0 in Fig. 1] and the feature (ii) due to decreasing μ (T) with increasing T, which takes place in undoped or weakly doped p-CdSb in the corresponding temperature interval [3,9].…”
Section: Analysis Of the Results And Discussionmentioning
confidence: 99%
“…We can rewrite this equation of four unknown parameters as an equation of two unknown parameters, , where μ * and R ∞ are fitting parameters with R 0 being R H ( B = 0). Using the zero field resistivity, R XX = ( en 1 μ 1 + en 2 μ 2 ) −1 , we can find the low-density-high-mobility (LDHM) ( n 2 and μ 2 ) and high-density-low-mobility (HDLM) ( n 1 and μ 1 ) carriers using , , , , , and 33 34 35 . The model fits at 50 and 2 K are shown by the black lines in the inset of Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Using the zero field resistivity, , we can find the low-density-high-mobility (LDHM) ( and ) and high-density-low-mobility (HDLM) ( and ) carriers using * , * / , * / , * * , , and . [33][34][35] The model fits at 50 and 2 K are shown by the black lines in the inset of Fig. 4 (b).…”
Section: Resultsmentioning
confidence: 99%